Avifaunistic’s Genetic Heat Index (GHI) of Four Landscapes in West Pasaman Regency, West Sumatra, Indonesia - Muhammad Nazri Janra; Aadrean Aadrean (Syiah Kuala University, 2018)
West Pasaman Regency in West Sumatra Province is recently established as an administrative area on 2003, segregated from Pasaman Regency where it was previously affiliated. This regency has been planning to support its structural developments using its main income generated from agricultural sector, which involve vast plantation area for oil-palm and other agricultural products. With the variety of its topography spans from some offshore islands up to 2,912 m mountain area, it is interesting to understand the importance value of this area from the perspective of one of its natural biodiversity: avifuna. Here in this paper, we use Genetic Heat Index (GHI) concept based on avian diversity and their conservation status to compare the significance value among four prominent landscapes in this regency, which include Mount Talamau and Laut Tinggal Lake (mountainous area), Tongar River (lowland-to-hilly riparian agricultural area) and Panjang Island (an offshore island). Despite the difference and similarity of bird species recorded in each site, Panjang Island has comparable GHI value with Tongar River, Mount Talamau and Laut Tinggal Lake (consecutively 4.20, 4.03, 4.14, 4.26). This result implies to the uniqueness of bird species living in each site along with its habitat typicality which also helps in contributing to their GHI value. Therefore, giving attention to this GHI concept while accommodate it into development plan will help in supporting more environmentally-sound development process.